Real breakthrough or pragmatic continuation? The Polish People`s Republic in the assessment of German diplomacy on the eve of imposing martial law in Poland - discussion theses - Jaskułowski, Tytus (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The author of the following Contribution text was interested in whether December 13, 1981 - it means also the Martial Law in Poland - really changed anything for West Germany from the point of view of its own foreign policy. The answers of this Question, formulated on the basis of the Research in the political archives of the West German Ministry of Foreign Affairs, aim at explaining the reasons for the behavior of certain institutions or politicians in West Germany after the breakthrough of 1980-1981.
Keywords: Germany; foreign policy; martial law; Polish People`s Republic; diplomacy; cold war